A Comprehensive Review on Bio-Based Polybenzoxazines Emphasizing Their Antimicrobial Property - Shakila Parveen Asrafali; Thirukumaran Periyasamy; Jaewoong Lee (Microorganisms)
Polybenzoxazines (PBzs), a class of high-performance thermosetting polymers, have gained significant attention for their exceptional thermal stability, mechanical properties, and chemical resistance, making them ideal for aerospace, electronics, and biomedical applications. Recent advancements emphasize their antimicrobial potential, attributed to unique structural properties and the ability to incorporate bio-active functional groups. This review highlights the synthesis, antimicrobial mechanisms, and applications of PBzs and their bio-based derivatives, focusing on sustainable materials science. PBzs demonstrate antimicrobial efficacy through mechanisms such as hydrophobic surface interactions and reactive functional group formation, preventing microbial adhesion and biofilm development. The incorporation of functional groups like amines, quaternary ammonium salts, and phenolic moieties disrupts microbial processes, enhancing antimicrobial action. Modifications with metal nanoparticles, organic agents, or natural bio-actives further augment these properties. Notable bio-based benzoxazines include derivatives synthesized from renewable resources like curcumin, vanillin, and eugenol, which exhibit substantial antimicrobial activity and environmental friendliness. Hybrid PBzs, combining natural polymers like chitosan or cellulose, have shown improved antimicrobial properties and mechanical performance. For instance, chitosan-PBz composites significantly inhibit microbial growth, while cellulose blends enhance film-forming capabilities and thermal stability. PBz nanocomposites, incorporating materials like silver nanoparticles, present advanced applications in biomedical and marine industries. Examples include zirconia-reinforced composites for dental restoration and urushiol-based PBzs for eco-friendly antifouling solutions. The ability to customize PBz properties through molecular design, combined with their inherent advantages such as flame retardancy, low water absorption, and excellent mechanical strength, positions them as versatile materials for diverse industrial and medical applications. This comprehensive review underscores the transformative potential of PBzs in addressing global challenges in antimicrobial material science, offering sustainable and multifunctional solutions for advanced applications.